2010
DOI: 10.1021/jf1000524
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Hop-Derived Monoterpene Alcohols by Lager Yeast and Their Contribution to the Flavor of Hopped Beer

Abstract: It is well-known that various beers contain many flavor compounds derived from barley malts, hops, yeast fermentation, and other raw materials. Among these flavor compounds, terpenoids are mainly derived from hops. Linalool, one of the monoterpene alcohols, has been found in various beers and been regarded as an important factor for a hop-derived beer flavor. We focus on contributions of other monoterpene alcohols (geraniol, beta-citronellol, nerol, and alpha-terpineol) to hopped beer flavor. Several researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 25 publications
12
119
0
4
Order By: Relevance
“…S. cerevisiae is able to convert the odourless linalyl glycoside to linalool via the action of β-glucosidases (38). Yeast has been shown to be able to convert geraniol to linalool (37,39), although geraniol was not detected in the wort.…”
Section: Changes In Volatile Compositionmentioning
confidence: 99%
“…S. cerevisiae is able to convert the odourless linalyl glycoside to linalool via the action of β-glucosidases (38). Yeast has been shown to be able to convert geraniol to linalool (37,39), although geraniol was not detected in the wort.…”
Section: Changes In Volatile Compositionmentioning
confidence: 99%
“…It had already been reported that the content of geraniol and β-citronellol in finished beer could be increased by enriching the initial geraniol content in the wort 27 . In beer production, hops (Humulus lupulus L.) are the main source of geraniol.…”
Section: Screening Of Geraniol-rich Hopmentioning
confidence: 99%
“…The flavour characteristics of monoterpene alcohols have also been reported 27 . Table I lists the olfactory descriptions of monoterpene alcohols and their group thresholds as determined by the sensory panellists.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations